2019
DOI: 10.1101/685172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of type 2 diabetes loci in 433,540 East Asian individuals

Abstract: SUMMARYMeta-analyses of genome-wide association studies (GWAS) have identified >240 loci associated with type 2 diabetes (T2D), however most loci have been identified in analyses of European-ancestry individuals. To examine T2D risk in East Asian individuals, we meta-analyzed GWAS data in 77,418 cases and 356,122 controls. In the main analysis, we identified 298 distinct association signals at 178 loci, and across T2D association models with and without consideration of body… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 80 publications
0
30
0
Order By: Relevance
“…Genome-wide association studies (GWAS) have been extremely successful in identifying T2D susceptibility loci but have mostly focused on populations of European ancestry ( 1-4 ). To address this population bias, more recent large-scale T2D GWAS have expanded into East Asian ancestry populations ( 5,6 ) and multi-ancestry biobanks ( 7,8 ). The DIAMANTE (DIAbetes Meta-ANalysis of Trans-Ethnic association studies) Consortium was established to assemble T2D GWAS across diverse populations and develop methodological blueprints for intra- and inter-ancestry meta-analyses relevant to any complex trait.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome-wide association studies (GWAS) have been extremely successful in identifying T2D susceptibility loci but have mostly focused on populations of European ancestry ( 1-4 ). To address this population bias, more recent large-scale T2D GWAS have expanded into East Asian ancestry populations ( 5,6 ) and multi-ancestry biobanks ( 7,8 ). The DIAMANTE (DIAbetes Meta-ANalysis of Trans-Ethnic association studies) Consortium was established to assemble T2D GWAS across diverse populations and develop methodological blueprints for intra- and inter-ancestry meta-analyses relevant to any complex trait.…”
Section: Main Textmentioning
confidence: 99%
“…The DIAMANTE (DIAbetes Meta-ANalysis of Trans-Ethnic association studies) Consortium was established to assemble T2D GWAS across diverse populations and develop methodological blueprints for intra- and inter-ancestry meta-analyses relevant to any complex trait. Analyses of the European and East Asian ancestry-specific components of DIAMANTE have previously been reported ( 4,6 ). Here, we describe the results of our trans-ancestry meta-analysis of T2D GWAS, which partially overlaps with these ancestry-specific efforts, focussing on genetic variation shared across population groups at loci robustly associated with the disease.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted that analyzing different ancestries can yield new insights into phenotypes ( SIGMA Type 2 Diabetes Consortium et al 2014 ; Wojcik et al. 2019 ; Spracklen et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies suggest a correlation between this inactivating mutation and several diseases including oral cancer, esophageal cancers, and blood and solid tumors associated with Fanconi anemia 7,8 . Importantly, several large-scale meta-analyses of genome-wide association studies revealed that this inactivating mutation is strongly associated with type 2 diabetes 9 , body mass index 10 , and serum lipids 11 in East Asians. A validation study further con rmed a close association of ALDH2*2 with visceral fat distribution in 2,958 Chinese subjects 12 .…”
Section: Introductionmentioning
confidence: 99%